Qualidade no atendimento: uma adaptação da escala servqual no Partage Shopping Mossoró - Batista, Diana Carla de Sousa (Universidade Federal Rural do Semi-Árido, 2020)
The trade war for expasion of markets, makes companies seek excellence in their services. Quality in customer service often becomes the focus in several businesses, especially those that aim to grow their profits. Mossoró city is important stand out in the commercial sector of the western region of Rio Grande do Norte, with this it has some commercial conglomerates, among which we highlight Partage Shopping Mossoró, the only one that stands out as a mall by the Associação Brasileira de Shopping Centers. This work aims to evaluate the quality of the service offered by Partage Shopping Mossoró. For this purpose, a questionnaire developed based on an adaptation of the SERVQUAL scale was used, guided by the following specific objectives: To identify the most fragile dimension of the SERVQUAL scale; Score stores with greater positive prominence in service quality; List suggestions for improvements based on the data collected. Questionnaires, a total were made available in virtual format, using the Google Forms platform, to Mossoro consumers who make use of the stores housed in that mall from October to November 2020. The collection instrument was designed to allow a quantitative analysis. With the data extracted, it was found that the mall in general offers a good level of quality in service, since all dimensions of the scale had averages above 3 points, on a scale ranging from 1 to 5. However, it should be noted that the empathy dimension proved to be the most fragile scale with an average of 3.4. Evaluating the stores mentioned in the survey, the one that stood out in the quality of service was Miranda Computação, with positive justifications focused on the efficiency of its employees.
Keywords: Qualidade no atendimento; SERVQUAL; Shopping; Service quality; Mall; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO